Learning Design for a Successful Blended E-learning Environment: Cultural Dimensions - Al-Huwail, N.; Al-Sharhan, S.; Al-Hunaiyyan, A. (INFOCOMP Journal of Computer Science, 2007)
Blended e-learning is becoming an educational issue especially with the new development of e-learning technology and globalization. This paper presents a new framework for delivery environment in blended e-learning. In addition, new concepts related to the learning strategies and multimedia design in blended e-learning are introduced. The work focuses on the critical cultural factors that affect a blended elearning system. Since it is common that good systems may fail due to cultural issues, this research work highlights these issues and how to utilize them to create a successful blended elearning. It introduces a new blended e-learning model that accommodates different cultural groups and various learning strategies.